1988
DOI: 10.1016/0014-5793(88)81372-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific opsonins for phagocytic cells and their different affinity for cholesterol‐rich liposomes

Abstract: In accordance with the finding of our in vivo experiments reported earlier [(1983) Biochim. Biophys. Acta 761,142-157; (1986) Biochim. Biophys. Acta 888, 184-190], the results of in vitro experiments show that Kupffer cells avidly take up cholesterol-poor but not cholesterol-rich liposomes, whereas splenic phagocytic cells take up preferentially cholesterolrich rather than cholesterol-poor liposomes in the presence of serum. Evidence presented here suggests that serum contains opsonins specific for hepatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(39 citation statements)
references
References 19 publications
1
37
0
1
Order By: Relevance
“…34) There are many reports regarding the binding of plasma proteins onto the surface of liposomes or emulsions and influence on their metabolic pathway. [35][36][37][38] Furthermore, the interaction of liposomes with serum components can cause the leakage of materials entrapped in the liposomes. 21,22) A number of studies have indicated that serum components increase the release efficiency of liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…34) There are many reports regarding the binding of plasma proteins onto the surface of liposomes or emulsions and influence on their metabolic pathway. [35][36][37][38] Furthermore, the interaction of liposomes with serum components can cause the leakage of materials entrapped in the liposomes. 21,22) A number of studies have indicated that serum components increase the release efficiency of liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…The major lipid components of all formulas were PC and CHO. CHO was used for almost half of the total lipids to provide more stable lipid bilayers to decrease the membrane fluidity as reported elsewhere (27,28). DCP and sodium DC were used as helper lipids to induce a negative surface charge on the liposomes.…”
Section: Chitosan-coated Liposome Preparation and Morphologymentioning
confidence: 99%
“…67 In addition to exposure to the environmental pollutants and 68 pathogens, the lung is also exposed to drug formulations that are 69 administered for the treatment of respiratory disorders. Recent 70 advancements in the technology for drug delivery have spurred a 71 growth in inhalational drug formulations with superior therapeu- 72 tic outcomes [5].…”
mentioning
confidence: 99%